(untitled) - Haythornthwaite, Caroline A; Andrews, Richard (Los Angeles, 2011)
Includes bibliographical references (p. [227]-254) and index; In 'E-learning Theory and Practice', the authors set out different perspectives on e-learning. The book deals with the social implications of e-learning, its transformative effects, and the social and technical interplay that supports and directs e-learning
Keywords: Computer-assisted instruction; Internet in education; Web-based instruction -- Social aspects; Hướng dẫn sử dụng máy tính; Mạng trong giáo dục; Đào tạo dựa trên mạng -- Khía cạnh xã hội; E-learning; Giáo dục trực tuyến